The occurrence of arbitrariness in linguistic phenomena (for example an opposites) - Alyaseri, أ.م.د حسام عدنان; Gazi , حلا مهدي (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The linguistic study is a wide scope، and a deep sea that is difficult to delve into، and it was associated with the Arabs with the need to understand the meanings of the Noble Qur’an. All aspects of the language lesson (phonetic، morphological، grammatical، and semantic)، with the focus of scholars and their interest in explaining the vocabulary of the Holy Qur’an and the Arabic language، and this led to the emergence of the idea of writing dictionaries، language books، and interpretations، whose authors sought to preserve this language through Their interpretation of the meanings of most of the vocabulary and their return to their origins، and this led to the abundance of literature and the multiplicity of opinions and the emergence and expansion of differences between scholars، and these differences were accompanied by their use of some critical terms and phrases، to express through them their objection and their response to some of these opinions، and among these terms is the term arbitrariness. Proceeding from this or others، we proceed to study an important aspect of the linguistic lesson، which is (arbitrariness) in the opinions of its linguists and their directives in (linguistic phenomena) to stand on a theoretical-procedural part through which we show the nature of this phenomenon and its evidence according to The analytical and normative descriptive approach، as the research is divided into two sections: the first: this paragraph included the concept of opposites، the reasons for its occurrence، and the scholars’ position on it. The second: was devoted to presenting the evidence in which abuse occurred in opposites. As we studied the multiplicity of opinions and attitudes that occurred in it، and the occurrence of (arbitrariness) in opposites، wherever it was found، and with the observation of comparison، balancing، and weighting of the right one، and criticism of the wrong one. These evidences were preceded by an introduction، and a preface، and then we followed the research with a conclusion in which we summarized the most important results، and then we included the margins and sources of the research..